2016
DOI: 10.15666/aeer/1401_111127
|View full text |Cite
|
Sign up to set email alerts
|

Plant Diversity-Environment Relationships in Xeric Grasslands of North-Eastern Romania

Abstract: Abstract. Dry grasslands are plant communities with major importance for biodiversity. In this study, xeric grasslands of the order Festucetalia valesiacae from North-Eastern Romania were analyzed, in 45 nested series, at seven grain sizes (0.0001-100 m 2 ), sampled in 5 plant communities within above mentioned phytosociological unit. The aim was to test the relative importance of different environmental factors on species richness (α-diversity) and species turnover (β-diversity), the last one expressed as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 47 publications
(57 reference statements)
1
5
0
Order By: Relevance
“…Additionally, species richness from a particular region is related to numerous factors and the effect of management type or different ecological factors on species richness is scale-dependent ( FernándezLugo et al, 2011 ; Li et al, 2015 ; Mardari, 2016 ). Species–area relationship (SAR) is among the best-documented pattern in community ecology and is frequently used to study diversity patterns across spatial scales ( FernándezLugo et al, 2011 ; Wilson, Peet & Dengler, 2012 ; Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, species richness from a particular region is related to numerous factors and the effect of management type or different ecological factors on species richness is scale-dependent ( FernándezLugo et al, 2011 ; Li et al, 2015 ; Mardari, 2016 ). Species–area relationship (SAR) is among the best-documented pattern in community ecology and is frequently used to study diversity patterns across spatial scales ( FernándezLugo et al, 2011 ; Wilson, Peet & Dengler, 2012 ; Li et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the community is the ideal unit for the development of a livable city. During the recent years, Taiwan has been proactively incorporated CO 2 emission reduction into community-based environmental protection policies such as the policy of forest plantation (Cabarga-Varona et al, 2016) with the purpose of improving air quality and building carbon stock of trees and providing incentives for plant diversity in idle spaces and parks within communities (Mardari and Tănase, 2016). Other policies provide incentives for green roof installation, roof-top solar power generation, and replacement with water-saving/power saving facilities.…”
mentioning
confidence: 99%
“…For example, Schultz et al [32] found that the effects of GE on plant species richness and phytomass accumulation varied across a regional productivity gradient. Species richness is scaledependent [33][34][35], especially the species-area relationship [36]. Li et al [37] reported that moderate grazing was a possible reason for the use of RG as a sustainable grazing management strategy.…”
Section: Introductionmentioning
confidence: 99%